Studies on inheritance of okra leaf shape and genetic parameters for morpho-yield related traits in two F2 populations of cotton (Gossypium hirsutum L.) - S. Surya Krishna1, M. Kumar2*, N. Premalatha1, K. Senguttuvan1 and L. Mahalingam1 (Indian Society of Plant Breeders, 2021)
The inheritance of leaf shape vis-a-vis specific leaf area and genetic parameter determining various morpho-yield related traits were studied in F2 populations of F2382 X CO17 and PBH115 x CO17 Wherein the female parent has okra type leaf and the male parent has a normal leaf. Leaf type was supposed to exhibit simple inheritance for 1:2:1 for normal leaf type, sub-okra leaf type and okra phenotypes showing incomplete dominance in both crosses. However, an attempt to associate leaf types with specific leaf areas across the segregants did not show any specific pattern indicating complexity in deducing the inheritance of specific leaf areas. Plant height, the number of bolls/plant and seed cotton yield per plant were highly variable traits. High heritability was observed for the traits viz., plant height, boll weight, ginning out turn, upper half mean length and uniformity ratio in both the crosses.